Peningkatan Minat Pelajar Sekolah Menengah Keatas di SMK Al-Hafiz untuk melanjutkan Pendidikan Ke Perguruan tinggi - Yusuf Iskandar; Jordan Chan William; Mochamad Khilmi; Dudih Gustian; Yudi Nata; Muhamad Muslih; Nunik Destria Arianti (LPPM Universitas Nusa Putra, 2023)
Students in Cikelat Village, Cisolok District, Sukabumi Regency have low interest in continuing their education to college. This can be seen from the data in the Cikelat village database. The reason the students in this village do not continue their education to college is the constraint in the form of the costs needed to continue to college, and the majority of them think that graduating from high school is enough to prepare them for the world of work. To solve this problem, an increase in interest in continuing school was held with technology learning videos in high school and above. This increase in the attractiveness of further school interest is carried out by giving presentations on how important it is to continue education to higher education, outlining the paths that can be taken to enter higher education, scholarships provided by universities and the government, as well as explaining the general description of higher education. Then at the end, a learning video will be given about the benefits and importance of continuing education to college. Keywords: interest, education, collegeStudents in Cikelat Village, Cisolok District, Sukabumi Regency have low interest in continuing their education to college. This can be seen from the data in the Cikelat village database. The reason the students in this village do not continue their education to college is the constraint in the form of the costs needed to continue to college, and the majority of them think that graduating from high school is enough to prepare them for the world of work. To solve this problem, an increase in interest in continuing school was held with technology learning videos in high school and above. This increase in the attractiveness of further school interest is carried out by giving presentations on how important it is to continue education to higher education, outlining the paths that can be taken to enter higher education, scholarships provided by universities and the government, as well as explaining the general description of higher education. Then at the end, a learning video will be given about the benefits and importance of continuing education to college.Keywords: interest, education, college